Physical characteristics of the hair coat of sows raised in free-range systems in a tropical environment - Nascimento, Sheila Tavares; Mós, João Victor Do Nascimento; Murata, Luci Sayori; Dos Santos, Vinicius Machado; Steidle Neto, Antonio José; de Oliveira, Evandro Menezes; Maia, Alex Sandro Campos [UNESP]; Teixeira, Bruno Emanoel; Parizotto, Raquel; Silva, Luana Freitas (Universidade Estadual de Maringa, 2024)
The aim of this study was to investigate the hair coat characteristics of sows raised in a free-range system in a tropical climate and assess associations with effective radiative properties and thermal conductivity. Bristles were collected from December 2017 to April 2018 and evaluated for diameter (mm), length (mm), and density (bristles per cm2). From these data, the effective thermal conductivity, absorptivity, transmissivity, and reflectivity of the hair coat were determined. Sows were separated into four groups according to skin pigmentation and color parameters. The environment was characterized with regard to average air temperature (°C), relative humidity (%), and shortwave radiation (W m-2). The data were analyzed by repeated measures analysis. Bristle length (33 mm) and density (10 bristles cm-2) were lower in summer than in colder months (48 mm and 20 bristles cm-2, respectively). Effective absorptivity was higher and transmittance was lower in more pigmented sows, demonstrating a connection with protection against solar radiation. Therefore, the combination of a pigmented and dense coat seems to be ideal for pigs reared in free-range systems.
Keywords: effective properties; hair coat; outdoor systems; swine; tropical climate